-4x2+3=-9

Simple and best practice solution for -4x2+3=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x2+3=-9 equation:



-4x^2+3=-9
We move all terms to the left:
-4x^2+3-(-9)=0
We add all the numbers together, and all the variables
-4x^2+12=0
a = -4; b = 0; c = +12;
Δ = b2-4ac
Δ = 02-4·(-4)·12
Δ = 192
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{192}=\sqrt{64*3}=\sqrt{64}*\sqrt{3}=8\sqrt{3}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-8\sqrt{3}}{2*-4}=\frac{0-8\sqrt{3}}{-8} =-\frac{8\sqrt{3}}{-8} =-\frac{\sqrt{3}}{-1} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+8\sqrt{3}}{2*-4}=\frac{0+8\sqrt{3}}{-8} =\frac{8\sqrt{3}}{-8} =\frac{\sqrt{3}}{-1} $

See similar equations:

| (6+x)×7=63 | | -4x8=52 | | -8=-7c | | 3m-15=-7.M=3 | | 5+2x-8+6x=-11. | | x÷7=-77 | | 2(3x-1)=3(2x-1) | | 43(x-7)=180 | | 8+40÷4×5−3=x | | 36.3=a-10.45 | | 13x-111=7x-57 | | 5-2(x+3)=-15. | | x/9-11=-7 | | 5=5x+-7 | | y+10y-24=0 | | 30v+36-6v-5=1 | | 24=f+4 | | 3^3x=243 | | 7-6=g | | w−12.1=7.53 | | 17=u+14 | | 2(x-3)+4x=18. | | 6a-2+3=-2 | | 20/300=x/40 | | 26=j+14 | | 3a+85=180 | | 10(1+3d)=−20 | | -1x+4x+3x=5x-8x+9x | | 6v-36=180 | | v=3.14(4)(8) | | 4x+1=9-2x-2x | | 44=5e-7 |

Equations solver categories